Of Being and Becoming: Psychoanalysis, Race and Class in an Urban ER. Issue 1 (1st January 2021) - Slevin, Michael
ABSTRACT: Psychoanalysis in the United States has traditionally been a practice of long-term, individual therapy conducted within the safe and comfortable surroundings of a consulting room. Through my work as a white man with a largely African American, low-income patient population in a hospital emergency room, I learned it can also be used in that fast-paced, crisis environment. Doing so, I learned, required a full engagement with my biases, cultural history, memories and personal traumas. It required understanding how structural racism is embedded in the work, the role it plays in defining my patients' reality coming into the ER, and their options once there. Although the first priority is to determine safety: Is the person in danger of harming themselves or another, if one broadens the scope of one's attention, as an analyst does, to the full person, do one's perspective, role and opportunities shift? I learned that I could do more than provide a descriptive diagnosis and disposition; I could actually begin the healing process. I learned I could better understand myself and my patients. The process was healing to both of us.